Single lung transplantation for end stage emphysema. Issue 5 (May 1995) - Briffa, N P; Dennis, C; Higenbottam, T; Nashef, S A; Large, S R; Wallwork, J; Wells, F C
Abstract : BACKGROUND-- The first successful single lung transplantation was carried out in 1983 for pulmonary fibrosis. Because of the inherent advantages of single lung transplantation, a transplantation programme has been started for patients with end stage lung disease due to emphysema. METHODS-- Between October 1990 and August 1993 25 patients with severe emphysema (15 men, mean age 51 years) received a single lung transplant at our institution. All patients were severely disabled with a mean (SD) 12 minute walking distance of 281 (165) metres. There were five deaths in the series, four in the first 20 days and one on day 503. Two patients suffered graft compression by air trapping in the native lung. Bronchial narrowing requiring insertion of endobronchial stenting occurred in four patients. RESULTS-- Mean (SD) FEV1 improved from a preoperative value of 17.8(13%) predicted to a six month value of 53.6(13)%, and FEV1/FVC from 23.8(12)% to 68.6(15)%. After the transplant 12 patients are in New York Heart Association (NYHA) class I and the rest of the survivors are in NYHA II. Actuarial survival was 82% at one year and 74% at three years. CONCLUSIONS-- Single lung transplantation is an effective treatment for end stage lung disease due to emphysema and carries an acceptable mortality and morbidity.